Association of Parasite Density and Hematological Parameters of Plasmodium vivax- and Plasmodium falciparum-infected Patients Attending Merauke General Hospital, Papua, Indonesia - Kurniawan, Roy Bagus; Wardhani, Puspa; Arwati, Heny; Aryati, Aryati; Butarbutar, Trieva Verawaty; Adiatmaja, Christophorus Oetama; Betaubun, Amarensi Milka; Chamidah, Nur (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Plasmodium falciparum and Plasmodium vivax are frequent causes of malaria. Although they are blood parasites, their biological characteristics are dissimilar, and their species-related consequences on hematological parameters have not been widely investigated. They might be valuable to distinguish both species infection, notably for an endemic region with limited diagnostic resources. AIM: This study aimed to know the species-specific effect on hematological parameters and its correlation to the parasite density in P. vivax- and P. falciparum-infected patients attending Merauke General Hospital, Papua, Indonesia. MATERIALS AND METHODS: Malaria patients confirmed by blood film microscopy from January 1 to July 31, 2019, were recruited, and their hematological parameters were measured using Sysmex XN-1000 instrument. All obtained data were analyzed statistically. RESULTS: From 100 malaria-positive patients, 87 patients, consisting of 57 P. vivax and 30 P. falciparum patients, met criteria. Anemia and parasite density >50,000 parasites/μL were significantly higher in P. falciparum than P. vivax patients (p < 0.05) though hemoglobin concentration and parasite density were insignificantly different. Interestingly, basophil count was significantly higher in P. falciparum compared to P. vivax patients (p = 0.04). The eosinophil count was significantly higher in P. vivax (p = 0.01) than P. falciparum patients and indicated a significant positive correlation (p = 0.04, r = +0.28) with the parasite density. CONCLUSION: There were significant differences between basophil and eosinophil count between P. vivax and P. falciparum infections. Eosinophil count showed a significant positive correlation with parasite density.